Empowering People and Planet: A Path to Sustainable Development, Poverty Eradication and Gender Equality - Ms. Anjali; Ms. Sakshi Chauhan (International Journal of Indian Psychȯlogy, 2022)
Since sustainable development has such a significant impact on bringing about radical changes in human society in all of its forms and because of the significant contribution it makes to many human and scientific sciences, it has drawn the attention of a large number of researchers. The study focuses on the concept of sustainable development it’s dimensions, goals and it’s importance in equal opportunities and poverty eradication. Economic expansion, social advancement, and environmental stewardship are all aspects of the multifaceted idea of sustainable development. It acts as a starting point for tackling global issues. Fair access to resources, opportunities, and social services is essential for eradicating poverty, a key goal of sustainable development. The importance of strengthening women and eliminating gender-based discrimination is highlighted by gender equality, a crucial component. This abstract examines the mutually reinforcing relationship between these dimensions, highlighting how empowering women and guaranteeing their full involvement in all aspects of life not only advance gender equality but also make a major contribution to the elimination of poverty and the pursuit of sustainable development as a whole. This investigation emphasizes the need for an integrated strategy that acknowledges the interconnectedness of these objectives in order to promote more inclusive and resilient communities through case studies and policy research.